The Decline of Class Actions - Robert H. Klonoff (Washington University Law Review, 2013)
This Article argues that in recent years courts have cut back sharply on plaintiffs’ ability to bring class action lawsuits, thereby undermining the compensation, deterrence, and efficiency functions of the class action device. Starting in the mid-1990s, courts began expressing concern about the pressure on defendants to settle after a decision certifying a class. The business community also raised concerns that many multi-state class actions were brought in pro-plaintiff, state-court venues. Federal Rule of Civil Procedure 23(f), adopted in 1998, enabled defendants to obtain interlocutory review of federal district court decisions certifying class actions, and the Class Action Fairness Act (CAFA), adopted in 2005, had the effect of shifting most major class actions to federal court. There is now a large body of federal appellate court case law, and as a result of that case law, several disturbing trends have emerged. First, many courts now require that plaintiffs prove substantial portions of their cases on the merits at class certification. Second, several of the class certification requirements (class definition, numerosity, commonality, adequacy of representation, Rule 23(b)(2), and Rule 23(b)(3)), are now considerably more difficult to establish. Third, a number of courts have rejected class settlements by rigidly applying the requirements for class certification, even though the settlement eliminates the need for a trial. Fourth, a number of courts have essentially nullified so-called “issues classes” under Rule 23(c)(4) by requiring courts to examine whether the case as a whole satisfies the predominance requirement of Rule 23(b)(3). Finally, the Supreme Court has upheld binding arbitration clauses that prohibit resolution of disputes on a classwide basis. Although some class actions remain viable, such as certain securities fraud, wage and hour, and antitrust class actions, the overall impact of these case law trends has been to curtail substantially the ability of plaintiffs to obtain class treatment. This Article thus concludes by urging courts, rule makers, and Congress to return to a more balanced approach to classwide adjudication.
Keywords: class action; Class Action Fairness Act; CAFA; certification; Rule 23